Laparoscopic simultaneous anterograde inguinal and pelvic lymphadenectomy for penile cancer: two planses, three holes, and six steps - Yi, Xian-lin; Li, Xiu-ning; Lu, Yu-lei; Lu, Hao-yuan; Chen, Yu; Zeng, Li-xia; Qin, Wen; Wu, Yun; Tang, Yong (Frontiers in Surgery, 2024)
Objective: To assess the feasibility, safety, and efficiency of simultaneous anterograde video laparoscopic inguinal and pelvic lymphadenectomy for penile cancer. Materials and methods: We reviewed retrospectively the records of 22 patients (44 lateral) who underwent inguinal lymph nodes dissection for penile cancer. The procedure was standardized as two planes, three holes, and six steps. Two Separate-planes: superior plane of eternal oblique aponeurosis/ / fascia lata; inferior plane of superficial camper fascia. Three holes: two artificial lateral boundary holes, the internal and external boundary holes, and the hole of oval fossa. Six steps: separate the first separate-plane; separate the second layer; separate two artificial lateral boundary holes; free great saphenous vein; separate the third hole and clean up the deep inguinal lymph nodes; pelvic lymphadenectomy. Results: A total of 22 cases were included and 9 patients underwent simultaneous pelvic lymphadenectomy. The average operation time on both sides was 7.52 ± 3.29 hours, which was 0.5 - 1 hour / side after skilled. The average amount of bleeding was 93.18 ± 50.84 ml. A total of 8 patients had postoperative complications, accounting for 36.36 %, and no complications great than Clavien-Dindo class III occurred. Conclusion: This study demonstrated that the video laparoscopic simultaneous anterograde inguinal and pelvic lymphadenectomy is a feasible and safe technique. Indocyanine Green was helpful for lymph node identify.